Boundary Works as a Mechanism For Forming Collective Identity in The Indonesian Middle Class Muslim Social Piety Movement - Saputra, Sahran; Ishomuddin; Wahyudi; Saleh, Arifin (Yayasan Ilomata, 2024)
Indonesia's title as the most generous country in the world is supported by the strengthening spirit of social piety movements among the Muslim middle class. Social piety movements are of course also supported by the power of the social movement's collective identity in forming the basis that provides the